The act of teaching - Cruickshank, Donald R. (McGraw-Hill, 2006)
The Act of Teaching prepares students to be competent beginning teachers and to develop into competent experienced teachers. Research-based, the text emphasizes what teachers need to know about students (how they learn and their diversities); how to plan and provide instruction; how to assess, manage and motivate students; and how, overall, to be an effective teacher. Well-designed pedagogical features prompt students to reflect on what they are learning, highlight current issues and topics, and encourage students to apply what they are learning.